Marketing margins for pineapple in the Philippines - Elcana, Ma. Elena G.
The study was conducted to examine marketing margins as one way of assessing the efficiency of marketing systems for pineapple in the Philippines, as well as problems involved and government policies, which could affect its competitiveness in the world trade. The study used annual data on farm, wholesale, and retail prices from 1975 to 1999 and used the models. Marketing margins at different levels were examined. The models were estimated using SPSS computer package test. Results showed that prices moved together. As farm prices increased, wholesale prices increased. As wholesale prices increased, retail prices increased, and as farm prices increased, retail prices increased. It was a sign of an efficient market. The margins showed a different picture. Margin from farm to wholesale did not change as farm prices increased, margin from wholesale to retail decreased as wholesale prices increased, and margin from farm to retail did not change as farm prices changed. Margin did not change when farm prices were involved. The implication is that farm prices were higher than wholesale prices in most instances, and farm prices were higher than retail prices in some cases. The common problem was on the road and infrastructure. There were programs that did not respond to the problems. Policies such as the EVAT and the 2.5% withholding tax greatly affected the competitiveness of pineapple in the world market as it led to high production cost, and thus, high export prices.